2016
DOI: 10.1007/s11883-016-0601-6
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Atherosclerotic Plaque Calcification: Translating Biology

Abstract: Calcification of atherosclerotic lesions was long thought to be an age - related, passive process, but increasingly data has revealed that atherosclerotic calcification is a more active process, involving complex signaling pathways and bone-like genetic programs. Initially, imaging of atherosclerotic calcification was limited to gross assessment of calcium burden, which is associated with total atherosclerotic burden and risk of cardiovascular mortality and of all cause mortality. More recently, sophisticated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 69 publications
0
19
0
Order By: Relevance
“…In addition, exosomes secreted by various cells, including macrophages, transporting MMP-2, MMP-3, MMP-9, and MMP-13, simultaneously contribute to vascular calcification. This increases plaque susceptibility to rupture, leading to life-threatening cardiovascular events such as myocardial infarction [35,[42][43][44]. Studies in patients with chronic kidney disease have shown that under mineral imbalance, there is an increased secretion of MMP-2-rich exosomes from vascular smooth muscle cells, which converts the exosomes into loci to endothelial calcification [45].…”
Section: Extracellular Vesicles As Mmps Carriersmentioning
confidence: 99%
“…In addition, exosomes secreted by various cells, including macrophages, transporting MMP-2, MMP-3, MMP-9, and MMP-13, simultaneously contribute to vascular calcification. This increases plaque susceptibility to rupture, leading to life-threatening cardiovascular events such as myocardial infarction [35,[42][43][44]. Studies in patients with chronic kidney disease have shown that under mineral imbalance, there is an increased secretion of MMP-2-rich exosomes from vascular smooth muscle cells, which converts the exosomes into loci to endothelial calcification [45].…”
Section: Extracellular Vesicles As Mmps Carriersmentioning
confidence: 99%
“…Not all forms of calcifications are equal with regard to intimal plaque vulnerability . While macrocalcification can act as biomechanical stabilizer, microcalcification or spotty calcification, regularly considered as less than 50 μm in diameter, confers high risk of atherosclerotic plaque rupture and is associated with poor prognosis . Microcalcification can be observed for instance with the use of intravascular ultrasound, an invasive imaging method requiring catheterization procedure .…”
Section: Vascular Calcificationmentioning
confidence: 99%
“…Microcalcification can be observed for instance with the use of intravascular ultrasound, an invasive imaging method requiring catheterization procedure . Clinical CT systems enable visualization of confluent areas of macrocalcification with good spatial resolution, however, the method lacks the sensitivity to sufficiently detect microcalcification . The recent advancement of combining CT and radionuclide‐based techniques such as positron emission tomography (PET) offers a promising solution to this .…”
Section: Vascular Calcificationmentioning
confidence: 99%
“…TCFA has a necrotic core and also calcium deposition [1,2]. Calcification is considered to be an active process, which involves information about vulnerability [14]. In fact, microcalcification or spotty calcification within the plaque is found to be the precursor of cardiovascular complications [15].…”
Section: S0mentioning
confidence: 99%